THE COMPETENCE POTENTIAL OF THE WORKFORCE UNDER THE INFLUENCE OF THE DIGITALIZATION OF THE ECONOMY - SHATALOVA, Liudmyla (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes the consequences of the influence of digital technologies on the competence potential of the workforce. The introduction of digital technologies determines the formation of megatrends that cause changes in the organization of business processes, social and labor relations, forms of employment, organization of the work process, principles of formation of the value of labor and its quality. The digital era is changing the role of humans in economic processes and makes it necessary to expand the competence potential, the basis of which is formed by the competence, skills and personal characteristics of potential employees. Especially important are the human properties that cannot be provided by digital technologies, in particular, cognitive competences. In non-standard situations typical of today's present, extra-professional qualities of a person become especially important. In the context of digital transformation, digital competence is of particular importance, as it will largely determine the ability of people to fulfill their professional duties and acquire competences in many other areas. Digital skills are the key to human coexistence with intelligent machines. The number of jobs requiring digital skills is increasing rapidly. The cost of not being able to acquire digital skills will increase over time. Micro-credentials will be a tool to promote lifelong learning, ensuring the flexibility and adaptability of the workforce to today's challenges, and reducing staff turnover.The development of the economy is impossible without the anticipatory development of human capital. Not only the level of material well-being of its bearer, but also the national wealth of the entire state depends on the level of competence potential of human capital.
Keywords: digitization of the economy; competence; cognitive skills; digital competences; micro-credential